Data on donation behavior towards the conservation of migratory species - Anna Lou Abatayo; Mathias Vogdrup-Schmidt; Jason F. Shogren; Niels Strange; Bo Jellesmark Thorsen (Data in Brief, 2023)
The data contains 716 individual decisions and responses from a lab-in-field experiment and an exit questionnaire that were conducted in Denmark, Spain, and Ghana. Individuals were initially asked to perform a small effort task (i.e., correctly counting the number of 1’s and 0’s in a page) to earn money and subsequently asked how much of their earnings they were willing to donate to BirdLife International to conserve Danish, Spanish, and Ghanaian habitats of the Montagu's Harrier, a migratory bird. The data is useful in understanding individual willingness-to-pay to conserve the habitats of the Montagu's Harrier along its flyway and could aid policymakers in having a clearer and more complete idea of support for international conservation. Among other things, the data can be used to look at the effect of individual socio-demographic characteristics and environmental and donation preferences on actual donation behavior.